2018
DOI: 10.1093/jxb/ery207
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the induction of phytoene synthase 2 expression by salt stress and abscisic acid in Daucus carota

Abstract: ABA increased during salt stress triggers binding of AREB/ABFs to DcPSY2 promoter, boosting carotenoid and ABA levels as a positive feedback mechanism

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 110 publications
(186 reference statements)
1
41
0
Order By: Relevance
“…Interestingly, exogenous ABA application induced PSY expression in Arabidopsis roots, leading to an increase in carotenoid accumulation (Meier et al ., 2011; Ruiz‐Sola et al ., 2014). Furthermore, a recent study showed that PSY2 expression was induced in carrot plants treated with ABA (Simpson et al , 2018). In addition, characterization of the DcPSY2 promoter revealed three ABA and GA regulatory elements (Simpson et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, exogenous ABA application induced PSY expression in Arabidopsis roots, leading to an increase in carotenoid accumulation (Meier et al ., 2011; Ruiz‐Sola et al ., 2014). Furthermore, a recent study showed that PSY2 expression was induced in carrot plants treated with ABA (Simpson et al , 2018). In addition, characterization of the DcPSY2 promoter revealed three ABA and GA regulatory elements (Simpson et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study showed that PSY2 expression was induced in carrot plants treated with ABA (Simpson et al , 2018). In addition, characterization of the DcPSY2 promoter revealed three ABA and GA regulatory elements (Simpson et al , 2018). Thus, higher GA and ABA contents in our tobacco lines might be responsible for the increased PSY expression (and probably the expression of other carotenoid genes) and the elevated carotenoid content.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al found that genes involved in the biosynthesis and signal pathway of ABA may be affected by carotenogenesis in carrot 137 . The expression level of DcPSY2 (phytoene synthase) can be induced by salt stress and ABA 138 . In Arabidopsis , salt stress was found to induce carotenoid synthesis to contribute to ABA production 139 .…”
Section: Hormone Regulationmentioning
confidence: 99%
“…The purpose of this study was not to examine abiotic stress tolerance but several studies have examined biochemical and molecular mechanisms underlying tolerance in carrot. Phytoene synthase is a key enzyme in the biosynthesis of carotenoid pigments critical for photosynthesis and its biosynthesis in carrot is upregulated under salinity stress (Fuentes et al., 2012; Simpson et al., 2018). A carrot heat shock protein contributing to heat tolerance was described in carrot (Malik, Slovin, Hwang, & Zimmerman, 1999) and several other carrot heat shock proteins have recently been described (Huang & Xu, 2008; Huang et al., 2015).…”
Section: Resultsmentioning
confidence: 99%